Determinants of Distance Walked during The Six-minute Walk Test in Patients Undergoing Valve Surgery in National Cardiovascular Center Harapan Kita, Indonesia - PA Syah (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
Background: A simple and efficient method to directly assess the functional capacity of the ...